1998
DOI: 10.1016/s1357-2725(98)00095-8
|View full text |Cite
|
Sign up to set email alerts
|

Properties and functions of the thiamin diphosphate dependent enzyme transketolase

Abstract: This review highlights recent research on the properties and functions of the enzyme transketolase, which requires thiamin diphosphate and a divalent metal ion for its activity. The transketolase-catalysed reaction is part of the pentose phosphate pathway, where transketolase appears to control the non-oxidative branch of this pathway, although the overall¯ux of labelled substrates remains controversial. Yeast transketolase is one of several thiamin diphosphate dependent enzymes whose three-dimensional structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
173
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(182 citation statements)
references
References 162 publications
(246 reference statements)
5
173
0
4
Order By: Relevance
“…Interestingly, the proposed reactions of the nonoxidative PPP are not firmly established; experimentally measured degree of 14 C isotope labelling and its distribution in carbon atoms of fructose-6-phosphate differs from that predicted by reaction sequences (Horecker et al, 1954;Williams et al, 1987;Schenk et al, 1998). This discrepancy demonstrates the presence of other types of nonoxidative PPP reactions, although the molecular and biochemical basis of these reactions remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the proposed reactions of the nonoxidative PPP are not firmly established; experimentally measured degree of 14 C isotope labelling and its distribution in carbon atoms of fructose-6-phosphate differs from that predicted by reaction sequences (Horecker et al, 1954;Williams et al, 1987;Schenk et al, 1998). This discrepancy demonstrates the presence of other types of nonoxidative PPP reactions, although the molecular and biochemical basis of these reactions remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Transketolase reaction is reversible, with the sole exception of cases where hydroxypyruvate is used as a substrate (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…TKT is known to encode an active transketolase enzyme (8), and TKTL2 is also likely to encode an active transketolase enzyme. TKTL1 has been assumed to be a pseudogene; however, it has been previously shown that TKTL1 could encode a transketolase-like protein (9).…”
Section: Introductionmentioning
confidence: 99%